Atmospheric phenomena in the Book of Sirach - Turkiel, Jan (Studia Ecologiae et Bioethicae, 2008)
Syrach in his book on atmospheric conditions speaks of their symbolic meaning. Frost is like sin, the beautiful weather that makes the frost disappear is a reward for mercy (Sir 3:15). Hail, snow, also falling fast, is a sign of their rule over the world (Sir 39, 29; 43, 13.15.18; 46, 5). Hoarfrost is a sign of their care for the earth (Sir 43:19). The heat symbolizes a gift offered with a harsh word (Sir 18:16). The only defense of such gifts is love for the Lord (Sir 34:16). Fog is a symbol of prudence, and a cure for bad weather is associated with a mysterious messenger (Sir 24: 3; 43, 22). Lightning and thunder are symbols of the appearance of a sage (Sir 32). , 10) A perishing thunder may be unjustly acquired as a symbol of wealth (Sir 40:13). But the thunder may be a symbol of their voice. It never goes away and continues with a powerful echo - the one who has not defiled himself with riches unjustly earns himself (Sir 43:17; 46.17,18.19).